Development of an Interactive Lifestyle Programme for Adolescents at Risk of Developing Type 2 Diabetes: PRE-STARt - Deirdre M. Harrington; Emer M. Brady; Susann Weihrauch-Bluher; Charlotte L. Edwardson; Laura J. Gray; Michelle Hadjiconstantinou; Janet Jarvis; Kamlesh Khunti; Itziar Vergara; Irati Erreguerena; Rogério T. Ribeiro; Jacqui Troughton; et al. (MDPI AG, 2021)
Background: Type 2 diabetes (T2D) is increasing in young people. Reporting on the processes used when developing prevention interventions is needed. We present the development of a family-based interactive lifestyle intervention for adolescents with risk factors for T2D in the future. Method: A multidisciplinary team in the UK site led the intervention development process with sites in Portugal, Greece, Germany and Spain. Potential programme topics and underpinning theory were gathered from literature and stakeholders. A theoretical framework based on self-efficacy theory and the COM-B (capability, opportunity, motivation, behaviour) model was developed. Sessions and supporting resources were developed and refined via two iterative cycles of session and resource piloting, feedback, reflection and refinement. Decision on delivery and content were made by stakeholders (young people, teachers, parents, paediatricians) and all sites. Materials were translated to local languages. Site-specific adaptations to the language, content and supporting resources were made. Results: The "PRE-STARt" programme is eight 90-min interactive sessions with supporting curriculum and resources. Iterative development work provided valuable feedback on programme content and delivery. Conclusion: Reporting on the intervention development process, which includes stakeholder input, could yield a flexible approach for use in this emerging 'at risk' groups and their families.